NASH-NASH IDEOLOGIS DALAM NOVEL WAJAH SEBUAH VAGINA KARYA NANING PRANOTO: PERKENALAN MARXISME SASTRA - Juanda (Jurnal Genta Mulia, 2017)
This research aims to analyze the ideologies contained in the novel Yohanes A Vagina by NP. This study is qualitative research. The research subjects are para novel characters, while the object of research is ideologies and the relationship between ideologies and social class. The data collection techniques used are observation, note-taking and documentation. Technique Data analysis is data collection, data reduction, data presentation, and drawing conclusions. Temporary Data validity testing techniques use source triangulation and member checking techniques. Research result are: (1) ideology divided into three types: (a) capitalism, (b) socialism, and (c) religion. (2) the relationship between social class and ideology, including: (a) social class in economics, (b) social class in socio-cultural, (c) social class in language, (d) social class in education, (e) social class in religion, and (f) class social in politics.